Study on the mechanical properties of nanoclay-epoxy composites under different hygrothermal aging conditions. (7th June 2019) - Shettar, Manjunath; Kini, U Achutha; Sharma, Sathyashankara; Hiremath, Pavan; Gowrishankar, M C
Abstract: The current study objectives to prepare and characterize nanoclay-epoxy composites (NECs) with a varying weight percentage of nanoclay. The NECs are prepared by mixing nanoclay and epoxy resin using a sonicator. The mixture is mold formed using direct casting technique, to make specimens as per ASTM standards. The specimens are treated with three hygrothermal aging conditions viz., cold water soaking, boiling water soaking and thermal shock. The properties of the specimens are characterized based on tensile and flexural tests as per ASTM standards. The results revealed that hygrothermal aging conditions have an adverse effect on the properties of neat epoxy. Addition of nanoclay increased the mechanical properties and decreased the effect of water soaking conditions. SEM images disclosed the reasons for the failure of the specimens. Conclusions are drawn based on comparison done in obtained results of dry specimens, and the specimens that underwent hygrothermal aging conditions.